Evaluasi Pendidikan Kecakapan Hidup Anak Usia dini di Taman Kanak-Kanak Se-Kecamatan Kroya - Wulaningsih, Arum (?ALI?A, 2018)
This research aims to describe the result of the evaluation of:context , input, process, and products of life skills education in early childhood kindergartens in Kroya Sub-district, Cilacap Regency. This research is evaluation research using the CIPP model developed by Stufflebeam, consisting of context, input, process, and product. A sample of 75 people consisting of 53 teachers and 22 principals was estabilished by using the inccindental sampling technique. The data were collected through a  uestionnaire, interviews, and observation. The validation of the instrument in term of context, input, process, and the product was determined by factor analysis. The Instrument reliability was determined by Cronbach Alpha formula. The data were analyzed by using the quantitative descriptive analysis. The quantitative data were processed with SPSS 20.0 for Windows and Microsoft Office Excel 2007. The research results are as follows: (1) Theresults of the evaluation context consists of the goal of life skill education teaching and parents’ participation in the life skill program is very good and consistent with the curriculum. (2) The results of the evaluation inputconsists of: educators’ education background on life skill education, educators’ qualification, educators’ competency  ackground, facilities and infrastructures, and financing is very good and consistent with the curriculum. (3) The results of the evaluation processes consists of planning,  plementation and appraisal is very good and consistent with the curriculum. (4) The results of the evaluation product of the implementation of child life skill education is very good and consistent with the curriculum.